Recent advances and challenges in solar photovoltaic and energy storage materials: future directions in Indian perspective. (27th July 2021) - Kartikay, Purnendu; Mokurala, Krishnaiah; Sharma, Bosky; Kali, Ravi; Mukurala, Nagaraju; Mishra, Dhananjay; Kumar, Ajit; Mallick, Sudhanshu; Song, Junyoung; Jin, Sung Hun
Abstract: The exponential increase in demand for global energy intake in day-to-day life directs us to look for a green and cost-effective energy generation and storage alternative. India being a fastly developing nation with a vast population, requires the alternative energy resource to meet up the energy deficit in an eco-friendly manner and be self-reliant in energy demands. This review aims to compile and assess developments in energy materials research from Indian prospects. Therefore, this paper discusses India's energy scenario by understanding the fundamental concepts and developments of various solar cell technologies and an overview of energy storage systems (batteries and supercapacitors), accentuating the research progress made so far along with future possibilities. This exploratory study reviews the systematic and sequential advances in all three generations of the solar cell, i.e. Si solar cell, thin-film solar cell, dye-sensitized solar cell, and perovskite solar cells. Herein, the discussion is directed at developing novel materials that are efficient, stable, and economical. Moreover, the current status of the high-performance devices for each technology is reviewed in detail. Finally, the prospects, areas of improvement, and future trends in developing cost-effective and efficient energy materials for solar cells and storage devices are highlighted.